P-HPB-09: A novel algorithmic approach for endoscopic ultrasound-guided biliary drainage based on factors influencing success of endoscopic ultrasound-guided transpapillary stenting - Dalal, Ankit (Endosc Ultrasound, 2017)
BACKGROUND AND OBJECTIVES: Endoscopic ultrasound-guided biliary drainage (EUS-BD) has emerged as an acceptable option for patients with failed endoscopic retrograde cholangiopancreatography (ERCP). However, it is not known that which of the multiple EUS-BD procedures is most appropriate in a given situation. Attempts at an algorithmic approach are hampered by sparsity of data about transpapillary procedures such as EUS-rendezvous (EUS-RV) and EUS-antegrade (EUS-AG) although published algorithms favor them over transluminal methods (choledochoduodenostomy or hepaticogastrostomy) as the first choice. To analyze factors influencing technical success of EUS-guided transpapillary stent placement through EUS-RV and EUS-AG procedures. To develop an algorithm for EUS-BD based on the results. METHODS: Data were collected retrospectively from two centers (India and Japan) over a 7-year period from 2009 to 2016. Records of patients who underwent transpapillary stenting via EUS-AG and EUS-RV procedures following a failed ERCP were entered in a uniform database. Collected data included procedural details, technical success, outcomes, and follow-up. Factors affecting technical success were analyzed by multivariate analysis. An algorithm was developed based on these results. RESULTS: A total of 197 patients underwent transpapillary stenting in the defined period (127 EUS-RV and 70 EUS-AG). Technical success was achieved in 181 patients (91.8%). There were 16 adverse events (8.1%). These included pancreatitis (2.5%), bile leak (2.5%), perforations (0.5%), and bleeding and cholangitis (1% each). One patient died in the EUS-RV group (0.5%). There was no significant difference in success and adverse events of EUS-RV and EUS-AG (success 92.9% vs. 90% P = 0.58, adverse events 7% vs. 10% P = 0.24). On multivariate analysis, common bile duct diameter was the only significant factor affecting success (t = 2.2. P = 0.029).